Performing Distance : the response of Irish professionals to immigrants and immigration - Byrne, Martina (Trinity College (Dublin, Ireland). Department of Sociology, 2014)
Literature on immigration in Ireland has focused on analyses of rates and flows, the impact of labour migration, immigrants’ experiences of racism and integration, and asylum/refugee studies. Empirical work on the response of the host population to immigration is dominated by studies on people occupying the lower levels of socioeconomic attainment. Such studies consistently argue that the lower classes are less tolerant toward immigrants and more likely to exhibit racist behaviour than other social classes due to real or perceived competition for economic resources and/or low levels of education. There have been no in-depth qualitative studies of the Irish professional class in this respect until now. This peer research study seeks to generate a substantive theory of how members of this class respond to immigrants and immigration. Reaching this objective requires examining how Irish professionals conceptualise contemporary immigration, eliciting the factors that influence how they respond to immigrants and immigration, and exploring their main concerns in such discussions. My research contributes to the literature on the intersection of race, ethnicity, and class and to the literature on a small, yet influential, section of the Irish population whose relative advantages include workplace decision making, political power, and access to influential social networks such as the media. I employ grounded theory methodology, with its emphasis on the emergence of new theory through data rather than testing ideas or existing theories. Iterative coding and analysis is informed by the grounded theory recommendation to go beyond ‘what arc people saying’ and explore ‘what is happening’. The interviewees were formerly my professional class peers and aged between 30 and 60. Fieldwork was conducted in 2008 and 2009, a period of socio-economic change in Ireland, substantial even by historic and international comparison. Based on my findings, I argue that the main concern of the Irish professional class, when discussing immigration, is to perform, and be seen to perform, the professional social class norms of tolerance and anti-racism. Dissonance between negative perceptions of some immigrants and some fellow-nationals on the one hand, and class norms of tolerance and anti-racism on the other, is managed through a process I conceptualise as Performing Distance, which, I argue, is operationalised through a range of discursive strategies deemed suitable for the public domain or ‘frontstage’: disclaiming, hierarchising, distancing, deflecting, and rationalising. Critically, the performance of racialising discourse is confined to the private domain or ‘backstage’ among trusted friends and family. Disclaiming refers to the Performance of Distance by claiming to know little or nothing about the subject. Hierarchising refers to indigenous, as well as foreign-born, groups in Irish society categorised and deemed more/less socially acceptable. Distancing from raced and classed others is further supported by descriptions of living and working in homogenous raced and classed spaces with no/few work colleagues, neighbours, or friends, who would be categorised as immigrants. Critically however, this study found that there exists an understanding of the term ‘immigrant’ which, while drawing on perceptions of racial and ethnic difference, distinguishes between people perceived to be in a position to contribute economically to the host state and groups deemed dependent, or potentially dependent, on state resources. Thus, professional class immigrants are not ‘real immigrants’. While immigration is presented as ‘not an issue’ for the higher social classes, it is perceived to ‘impinge’ on the lower social classes who are understood to be in competition for resources such as jobs and welfare. Thus the ‘problem’ of immigration is deflected on to the Irish lower social classes. When immigration is problematised, the rhetoric of rationality is used, grounded mainly in economic arguments and, to a lesser extent, in a perceived threat to Irish cultural identity. Finally, racialising refers to my finding of a ‘backstage’ discourse which employs racial terms, stereotypes and tropes.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin